Hashimoto’s Encephalopathy in a Pediatric Female: Time to Revisit This Diagnosis - Jadhav, Toyaja M; Patil, Sunita (Annals of Pathology and Laboratory Medicine, 2024)
Hashimoto’s encephalopathy (HE) is an infrequent encephalopathy of presumed autoimmune origin characterized by high titres of antithyroid antibodies. It is common in females, and although it is seen across all age groups, it is relatively uncommon among the paediatric population, with a prevalence of only about 1.2%. Hashimoto’s encephalopathy is a rare complication of Hashimoto’s thyroiditis and presents with a syndrome of persistent fluctuating neurologic and neuropsychologic deficits associated with elevated antithyroid antibodies, specifically thyroid peroxidase (TPO) antibodies. We present one such case of Hashimoto’s encephalopathy, diagnosed in an 11-year-old female, which mimicked brain death, along with a review of the available literature.